KAJIAN SENSASI KENYAMANAN TERMAL DAN KONSUMSI ENERGI DI TAMAN SRIGUNTING KOTA LAMA SEMARANG - Suyono, Bambang; Prianto, Eddy (MODUL, 2018)
An active park is indicated by the people activities and supported by the elements of street furniture. Hardware and software elements are the inside parts which play an important role in creating the comfort, wherein supported by the sustainability of the exterior gardens (outside the building) in the tropics play a very important role in the microclimate environment. The phenomenon of the relationship between conservation of ancient areas in the tropics such as Semarang city and the national energy crisis in the last decade is very interesting to be explored. As the development of instructional subject matter of Advance Landscape, Architecture Design and Building Physics in the basic of this research, our research question is: How far is the relationship between the energy profile consumption (lamp lighting) to comfort in the park?Two methods used in the field observation, the measurement of climate aspect to find out the micro climate profile and the distribution of questionnaire in the park to discover the user comfort sensation. The results found Taman Srigunting in the old city of Semarang is categorized both as a passive and active park, used for prominent activity in photography. These parks also influence the surrounding nature by decreasing the microclimate such as air temperature and humidity in the evening in the amount of 76% and 57% in the day. The air temperature went down from 34.8 C to 28.7 C. The micro climatic conditions and characteristics of energy consumption level was significant with the visitors comfort sensations, where inÂ  56% visitors felt comfortable and only 4% felt the sensation of heat.